Ex vivo and in silico evaluations of (E)-5-((benzo[d]thiazol-2-ylimino)(methylthio)methylamino)-2-hydroxybenzoic acid as a β3-adrenoreceptor agonist exerting anti-obesity, anti-inflammatory and hepatoprotective effects on Zucker rats - Laura Cristina Cabrera-Pérez; Itzia Irene Padilla-Martínez; Ángel Miliar-García; Modesto Gómez-López; Marina Olivia Franco-Hernández; Jessica Elena Mendieta-Wejebe; Martha Cecilia Rosales-Hernández (PLoS ONE, 2026)
Obesity increases oxidative stress and inflammation and thereby promotes liver damage and metabolic disorders, such as type 2 diabetes. Although exist anti-obesity treatments with employing anorexic drugs, antioxidants, and β3-adrenergic receptor (β3-ADR) agonists, their use adversely effects human health. Herein, the agonistic effect of 5-(((benzo[d]thiazol-2-ilimino)(methylthio)methyl)amino)-2-hydroxybenzoic acid ( C1 ) on β3-ADRs as well as its hepatoprotective and anti-inflammatory properties are investigated in obese Zucker rats. When compared to clobenzorex, C1 (12 mg/Kg bodyweight per day) intragastrically administered for 28 days significantly reduced the bodyweight and daily growth of the animals ( p < 0.0001), as it stimulated thermogenesis by activating the uncoupling protein 1 (UCP-1) ( p = 0.0090), which was mediated by the positive expression of β3-ADR ( p = 0.0149). C1 -induced β3-ADR activation was attributed to the formation of conventional hydrogen bonds between the hydroxyl and secondary amine groups of C1 with ASP117, VAL121, and THR122 at the catalytic site on the receptor. In addition, C1 significantly decreased the levels of free fatty acid ( p < 0.0001) and tumor necrosis factor alpha ( p = 0.0073). Furthermore, C1 increased glutathione levels ( p = 0.0245), and showed a tendency to decrease lipid oxidation and interleukin 6 levels. Therefore, these findings nevertheless suggested that C1 acted as a β3-ADR agonist and exerted hepatoprotective and anti-inflammatory effects on obese Zucker rats.